Tingkat Kesehatan Bank : Analisa Perbandingan Pendekatan CAMELS Dan RGEC (Studi Pada Bank Umum Syariah Tahun Periode 2012-2014) - Arif Rachman Husein; Fatin Fadhilah Hasib (Jurnal Ekonomi Syariah Teori dan Terapan, 2016)
The aim of this study was to determine whether there is difference in the level of health of Islamic Banks using CAMELS method approach and RGEC period 2012-2014. The method used is quantitative method with purposive sampling technique. This study uses eight Islamic Banks; Bank Muamalat Indonesia, Bank Syariah Mandiri, BNI Syariah, Bank Mega Syariah, BCA Syariah, BRI Syariah, Bank Panin Syariah Bukopin Syariah. The data used are secondary data by collecting the data of annual financial statements and GCG report in the period 2012-1014, then test the difference by using the Wilcoxon test.The research found that there are differences in the level of health of Islamic Banks using CAMELS method and RGEC method.